High Fasting Blood Glucose Level With Unknown Prior History of Diabetes Is Associated With High Risk of Severe Adverse COVID-19 Outcome - Wang, Wenjun; Chai, Zhonglin; Cooper, Mark E.; Zimmet, Paul Z.; Guo, Hua; Ding, Junyu; Yang, Feifei; Chen, Xu; Lin, Xixiang; Zhang, Kai; Zhong, Qin; Li, Zongren; et al. (Frontiers in Endocrinology, 2021)
Background We aimed to understand how glycaemic control among COVID-19 patients may impact their disease progression, clinical complications and adversities. Methods We enrolled 2,366 COVID-19 patients from Huoshenshan hospital in Wuhan. We stratified the COVID-19 patients into four subgroups by current fasting blood glucose (FBG) levels and prior diabetic status, including patients with FBG<6.1mmol/L with no history of diabetes (group 1), patients with FBG<6.1mmol/L with a known history of diabetes diagnosed (group 2), patients with FBG≥6.1mmol/L with no history of diabetes (group 3) and patients with FBG≥6.1mmol/L with a known history of diabetes (group 4). A multivariate cause-specific Cox proportional hazard model was used to assess the associations between FBG levels or prior diabetic status and clinical adversities in COVID-19 patients. Results COVID-19 patients with higher FBG and unknown diabetes in the past (group 3) are more likely to progress to the severe or critical stage than patients in other groups (severe: 38.46% vs 23.46%-30.70%; critical 7.69% vs 0.61%-3.96%). These patients also have the highest abnormal level of inflammatory parameters, complications, and clinical adversities among all four groups (all p<0.05). On day 21 of hospitalisation, group 3 had a significantly higher risk of ICU admission (14.1% [9.6%-18.6%]) than group 4 (7.0% [3.7%-10.3%]), group 2 (4.0% [0.2%-7.8%]) and group 1 (2.1% [1.4%-2.8%]), (P<0.001). Compared with group 1 who had low FBG, group 3 demonstrated 5 times higher risk of ICU admission events during hospitalisation (HR=5.38, 3.46-8.35, P<0.001), while group 4, where the patients had high FBG and prior diabetes diagnosed, also showed a significantly higher risk (HR=1.99, 1.12-3.52, P=0.019), but to a much lesser extent than in group 3. Conclusion Our study shows that COVID-19 patients with uncontrolled current FBG levels accompanied by pre-existing but unaware diabetes, or possibly new onset diabetes as a result of COVID-19 infection, have a higher risk of more severe adverse outcomes.